Lifestyles of Intellectually Disabled Adults - Bąbka, Jarosław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Jarosław Bąbka, Lifestyles of Intellectually Disabled Adults. Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 217–235. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/ 10.14746/ikps.2019.26.10 The purpose of the paper is to show lifestyles of intellectually handicapped adults in the context of the Andrzej Siciński concept. The paper presents the results of research carried out following the interpretive trend, in the hermeneutic-phenomenological perspective, using the dialogue method. The study shows that the disabled manifest habits indicating a blocked, withdrawal as well as a here-and-now-oriented style. The analysed persons exhibited a searching style only in a small extent. There were no statements indicating a change-oriented style. The respondents adapted passively to the conditions of their lives, they were reluctant to speak about the future and about the need to change something in their own lives. The analysis and interpretation of the research results revealed three incompatible areas: (1) culture patterns (the way of thinking, norms of functioning in a particular community), (2) resources of their environment, and (3) resources of an individual, which explains why the lifestyles of intellectually handicapped people analysed in the study were oriented towards passive adaptation rather than to development and changes.